Exploring the Dynamics of 'Pemelajar' and 'Pembelajar': A Corpus Linguistic Analysis in BIPA - Elis Ariesa Rani; Pratomo Widodo; Titik Sudartinah (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2025)
This article study aims to identify the usage frequency, analyse the usage context, compare usage patterns, and provide recommendations for teaching Indonesian as a Foreign Language (BIPA), with the focus on the terms pemelajar and pembelajar. Utilizing corpus analysis with AntConc, the term pemelajar is found to appear 697 times, whereas pembelajar appears 168 times across twenty distinct texts. The KWIC (Key Word in Context) analysis reveals that pemelajar frequently refers to BIPA students in instructional and descriptive contexts, with collocations such as diminta, dalam, and bipa. In contrast, pembelajar is used in more formal contexts related to the BIPA learning process, with collocations including bipa, bahasa, and dalam. N-Gram analysis indicates that the phrase "pemelajar bipa" is the most frequently occurring, suggesting a preference for its use in informal contexts. Based on these findings, it is recommended that BIPA instruction place greater emphasis on using the term pemelajar in instructional materials and curricula. Furthermore, it is advised that explanations of the contextual differences and usage of these terms be included in BIPA teacher training modules to enhance understanding and teaching effectiveness. This research offers practical guidance for BIPA educators in selecting appropriate terminology and strengthens Indonesian language instruction by providing a deeper understanding of the context and frequency of these key terms.